Integrablility of a classical N=2 super sinh-Gordon model with jump defects - Gomes, J. F. [UNESP]; Ymai, L. H. [UNESP]; Zimerman, Abraham Hirsz [UNESP] (Springer, 2008)
The Lagrangian formalism for the N = 2 supersymmetric sinh-Gordon model with a jump defect is considered. The modified conserved momentum and energy are constructed in terms of border functions. The supersymmetric Backlund transformation is given and an one-soliton solution is obtained.The Lax formulation based on the affine super Lie algebra sl(2, 2) within the space split by the defect leads to the integrability of the model and henceforth to the existence of an infinite number of constants of motion.
Keywords: integrable hierarchies; integrable field theories